A textbook of engineering mechanics - Kumar, D.S. (New Delhi, India : S.K. Kataria & Sons, 2012)
The study of this subject is aimed at developing a thorough understanding of the basic concepts and principles of mechanics and their application to solve engineering problem.
1. Basic Concepts -- 2. Two-dimensional Con-current force systems --3. Two-dimensional Non-current Force systems. -- 4. Friction -- 5. Structure: Trusses and frames -- 6. Centre Points: Centroid and Centre of Gravity -- 7. Moment of Inertia: Area and Mass -- 8. Rectilinear and Curvilinear -- 9. Rotation and general plane motion -- 10. Kinetics: Impulse, Momentum, work and energy. -- 11. Kinetics of Rotary Motion -- 12. Virtual work.
Reprint 2019.
Includes index.
Keywords: ENGINEERING MECHANICS